Academic Mothers Building Online Communities It Takes a Village - Trocchio, Sarah; Hanasono, Lisa K.; Borchert, Jessica Jorgenson; Dwyer, Rachael; Harvie, Jeanette Yih. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This volume focuses on the diverse ways in which mothers working within academia seek to find others with similar experiences to build virtual communities. Although the faculty and student populations of universities have diversified, mothers in academia are disproportionately overrepresented in precarious faculty and staff positions and continue to experience myriad institutional and interpersonal barriers, such as gender wage gaps that are exacerbated by stop-the-clock tenure policies, inadequate parental leave policies, expensive or scarce local childcare options, and social biases. The book gives space to the many ways women create and challenge their own versions of motherhood through a digital "village," examining how academic mothers use virtual communities to seek and enact different kinds of support.
1. It Takes a Village: Academic Mothers Building Online Communities -- Part I Identity and Marginalization -- 2. How Finding Identity with an Online Community Led to Advocacy -- 3. (Un)Supported: Challenges and Opportunities Experienced by Academic Mothers of Color in Online Communities -- 4. Barefoot Strangers: Multinational Digital Epistemologies of Academic Moms, Mamás, Mamy, Umahat -- 5. Creating an Online Community of Support: Mothers of Children with Disabilities Working in the Academy -- 6. Who Is There When Everything Changes?: The Anchoring Effect of Online Maternal Support Groups During Periods of Liminal Professional Identity -- 7. How Academic Mothers Experience Face Threatening Acts and Reinforcing Facework on Instagram -- 8. #GradStudentMom Finds Community Online -- 9. Being Alone Together: The Affordances and Constraints of Social Media Groups for Single Moms -- Part II Connection and Support -- 10. Dealing with Death inAcademia, or When 11,000 Mamas* Had my Back -- 11. The Face(book) of Academic Motherhood: Online Communities Respond to the Traumatic and the Mundane -- 12. Hell Hath No Fury Like a Scorned Woman's Friend: Reflected Anger in Academic Mother* Online Groups -- 13. Online Groups as Source for Communication about the Taboo: Sexual Implications for Academic Mothers* -- 14. Social Support Theory: Physical Isolation and Academia with Children -- Part III Pandemic Parenting -- 15. Building Welcoming Spaces on Social Media: Motherhood in Academia During a Pandemic and Beyond -- 16. Drafting while Drifting: Developing a Digital Village of Support and Advocacy During the COVID-19 Pandemic -- 17. Building a Virtual Village: Academic Mothers'* Online Social Networking During COVID-19 -- 18. The First Rule about Writing Group: How a Virtual Writing Group Changed My Trajectory Without Saying a Word -- 19. "Comedy and Tragedy," or How We Used Our Group Chat to Fill the Pandemic Care Gap -- 20. Kids at the Door: An Autoethnography of Our Shared Research Identity as Academic Mothers in Virtual Collaboration.
Keywords: Education, Higher; Sex; Educational sociology; Education -- Economic aspects; Educational technology; People with disabilities -- Education; Higher Education; Gender Studies; Sociology of Education; Education Economics; Digital Education and Educational Technology; Education and Disability